Physical activity and sedentary lifestyle towards teenagers’ overweight/obesity status - Kurdaningsih, Septi Viantri; Sudargo, Toto; Lusmilasari, Lely (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevalence of obesity and overweight that caused by genetic factor and environment factors, like physical activity and sedentary lifestyle, increased continually, not only in children and teenagers who live in developed countries, but also in developing countries. Aim of this research was to understand the relation of physical activity and sedentary lifestyle towards teenagers’ overweight/obesity status of State Senior High School in Yogyakarta City, Indonesia. Methods:This research was an observational research using cross-sectional method. Samples in this research were 184 State Senior High School students in Yogyakarta between July-August 2015 with proportional stratified random sampling method. Data was analyzed using chi-square test and multiple logistic regressions. Results: There was relation between physical activity and overweight/obesity (p<0.001), also between sedentary lifestyle and overweight/obesity (p<0.001). Analysis result of multiple logistic regressions showed that dominant factors in this research were family income, parents’ overweight history, physical activity, and sedentary lifestyle with p<0.001 and R square 0.539. Conclusions:Overweight/obesity in teenagers could be caused by the decreased physical activity and the increased sedentary lifestyle, and aggravated by family income and parents’ overweight history. Follow up research must be done using cohort study design with bigger samples.